2011
DOI: 10.1073/pnas.1101263108
|View full text |Cite
|
Sign up to set email alerts
|

HER2 overcomes PTEN (loss)-induced senescence to cause aggressive prostate cancer

Abstract: Prostate cancer (CaP) is the most common cancer among adult men in the Western world. Better insight into its tumor-activating pathways may facilitate the development of targeted therapies. In this study, we show that patients who develop prostate tumors with low levels of PTEN and high levels of HER2/3 have a poor prognosis. This is functionally relevant, as targeting Her2 activation to the murine prostate cooperates with Pten loss and drives CaP progression. Mechanistically, this is associated with activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 47 publications
5
53
1
Order By: Relevance
“…Indeed, our group showed that combined deletion or mutation in p53 cooperates with pten deficiency to accelerate aggressive, transplantable TNBC-like tumors (13,62). As noted, prostatespecific inactivation of pten also induces benign tumors with increased p53-dependent senescence (11,12). Likewise, in models of biliary tract malignancies and von Hippel-Lindau (VHL) disease, murine pten inactivation either fails to induce tumors or elicits low-grade lesions (65,66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our group showed that combined deletion or mutation in p53 cooperates with pten deficiency to accelerate aggressive, transplantable TNBC-like tumors (13,62). As noted, prostatespecific inactivation of pten also induces benign tumors with increased p53-dependent senescence (11,12). Likewise, in models of biliary tract malignancies and von Hippel-Lindau (VHL) disease, murine pten inactivation either fails to induce tumors or elicits low-grade lesions (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…In PTEN hamartoma tumor syndromes (PHTSs) like Cowden and Bannayan-RileyRuvalcaba, inherited autosomal mutations in PTEN lead to noncancerous tumor-like growths called hamartomas (10). In mouse models, prostate-specific inactivation of pten induces benign tumors with increased senescence, which is bypassed by concomitant inactivation of the tumor suppressor p53 (11,12). While pten deletion in mouse mammary epithelium leads to tumor formation (13), little is known about the tumorigenic potential of these lesions or of cooperating oncogenes/tumor suppressors that induce malignant…”
Section: Introductionmentioning
confidence: 99%
“…Failing to detect significant mutations or amplifications of RTKs, integrated genomic analyses have highlighted the involvement of PI3K/AKT and RAS/ERK pathways at a relatively high frequency (43%) in primary PC and almost universally in metastatic disease (2). Dual activation of PI3K and RAS pathways has been implicated in bypassing primary tumorsuppressive responses such as growth arrest and senescence (3,4). Interestingly, expression of phosphatase and tensin homolog (PTEN) and sprouty2 (SPRY2), key negative feedback regulators of the PI3K and RAS cascades, is decreased at higher frequencies than mutational activation of oncogenes such as PI3KCA, KRAS, and BRAF (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…Several genes cooperate with Pten loss to induce tumorigenesis in mice, including either loss of tumor suppressors such as Smad4 or Tp53 or activation of Erbb2 or Erg. However, none of these tumors fully reflect the continuum of human CaP (6)(7)(8)(9).…”
mentioning
confidence: 99%